Skin over the centuries. A short history of dermatology: physiology, pathology and cosmetics - Santoro, Rosa (Medicina Historica, 2017)
Dermatology, as a specialized branch of medicine dealing with skin, has a relatively short history. However, skin itself has an ancient history. The paper, divided into six sections (Introduction; The language of the skin; The skin and anatomy; Skin diseases; Beauty of the skin: Cosmetics; Conclusion), aims to demonstrate that the linguistic and epistemological foundations of modern science are rooted in Greek and Roman medicine.